ANALISIS NILAI MORAL DALAM CERPEN ANAK “PETUALANGAN BANYU KE NEGERI JAUH” KARYA SRI HANDAYANINGSIH DALAM MENINGKATKAN KARAKTER SISWA SEKOLAH DASAR - Rian Sani; Indra Permana; Sary Sukawati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The study focused on learning the moral values contained in the children's storybook "the adventure of banyu to a distant land" by sri handayaningaiah as one of the textbooks that could improve the character of the reader. The goals that will be reached in this study to analyze and describe the moral values that serve as a message ora commission that can serve as a lesson to the reader delivered by the writer. The objective of this short story was that of school-age children in the 1st, 2nd and 3rd grade elementary school children, this booklet also trains character education in children. The type of research used is qualitative descriptive research. The result of material analysis is that conclusions use words instead of Numbers and data collection techniques through the narrative structural data analysis found in the story. The moral value of the story is that of positive morals conveyed by negative incidents or events experienced by the figure banyu as water. If associated with elementary student character, then moral value in the story provides the message of doctrine in preserving the environment.